MiR-4775 promotes colorectal cancer invasion and metastasis via the Smad7/TGFβ-mediated epithelial to mesenchymal transition. Issue 1 (December 2017) - Zhao, Senlin; Sun, Hongcheng; Jiang, Weiliang; Mi, Yushuai; Zhang, Dongyuan; Wen, Yugang; Cheng, Dantong; Tang, Huamei; Wu, Shaohan; Yu, Yang; Liu, Xisheng; Cui, Weiyingqi; et al.
Abstract Background Despite advancements in the diagnosis and treatment of colorectal cancer (CRC), many patients die because of tumor metastasis or recurrence. Therefore, identifying new prognostic markers and elucidating the mechanisms of CRC metastasis and recurrence will help to improve the prognosis of the disease. As dysregulation of microRNAs is strongly related to cancer progression, the aim of this study was to identify the role of miR-4775 in the prognosis of CRC patients and the underling mechanisms involved in CRC progression. Methods qPCR and in situ hybridization were used to evaluate the expression of miR-4775 in 544 pairs of paraffin-embedded normal and CRC tissues. Kaplan–Meier analysis with the log-rank test was used for survival analyses. Immunohistochemical staining was applied to investigate the expression of miR-4775-regulated Smad7/TGFβ pathway-associated markers. In vitro and in vivo invasion and metastasis assays were used to explore the function of miR-4775 in the progression of CRC. Results miR-4775 was identified as a high-risk factor for CRC metastasis and recurrence, with high levels predicting poor survival among the 544 studied CRC patients. Furthermore, high miR-4775 expression promoted the invasion of CRC cells as well as metastasis and the epithelial to mesenchymal transition (EMT) via Smad7-mediated activation of TGFβ signaling both in vitro and in vivo. Downregulating miR-4775 or overexpressing Smad7 reversed the tumor-promoting roles of miR-4775/Smad7/TGFβ in vitro and in vivo. Conclusion miR-4775 promotes CRC metastasis and recurrence in a Smad7/TGFβ signaling-dependent manner, providing a new therapeutic target for inhibiting the metastasis or recurrence of the disease.